2017
DOI: 10.1007/s00167-017-4671-y
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of improved movement technique after receiving verbal external focus and video instruction

Abstract: PurposeIt is unknown how movement patterns that are learned carry over to the field. The objective was to determine whether training during a jump-landing task would transfer to lower extremity kinematics and kinetics during sidestep cutting.MethodsForty healthy athletes were assigned to the verbal internal focus (IF, n = 10), verbal external focus (EF, n = 10), video (VI, n = 10) or control (CTRL, n = 10) group. A jump-landing task was performed as baseline followed by training blocks (TR1 and TR2) and a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 27 publications
4
49
1
Order By: Relevance
“…Since internal cues may worsen performance 10 and external cues have been shown to improve kinematics during jump training, perhaps the cues on the task card should focus the athlete's attention externally and not internally. 27,32 For example, keeping the externally focused cues (i.e., land quietly) and changing internally focused to externally focused cues may augment learning to land softly without decreasing jump height performance. 35 Evidence also suggests that twodimensional external cues (i.e., keep markers on knees apart) may help avoid a dynamic limb valgus position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since internal cues may worsen performance 10 and external cues have been shown to improve kinematics during jump training, perhaps the cues on the task card should focus the athlete's attention externally and not internally. 27,32 For example, keeping the externally focused cues (i.e., land quietly) and changing internally focused to externally focused cues may augment learning to land softly without decreasing jump height performance. 35 Evidence also suggests that twodimensional external cues (i.e., keep markers on knees apart) may help avoid a dynamic limb valgus position.…”
Section: Resultsmentioning
confidence: 99%
“…First, the significant decrease in vGRF during single limb landings suggests that training athletes to land softly during a single limb task is not required in addition to task training when landing on both limbs. Others 27 have found that movement training during jump landing tasks transferred to cutting tasks. Second, the statistically significant decrease in vGRF impulse over time for the single limb drop jump (i.e., decrease of 0.32 Ns/kg) is likely clinically meaningful as it equates to a 15% difference from pre-to post-intervention (i.e., [{Post vGRF -Pre vGRF}/Pre vGRF] * 100).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, relative to enhanced expectancies and autonomy support, the potential benefits of an external focus have received considerably more discussion with respect to ACL injury prevention programs and injury rehabilitation [22,75,76,79,80], yet still have limited support from empirical data, particularly for patients following ACLR. Though a few additional studies have examined the effects of an external focus for improving biomechanics associated with ACL injury risk [23,24,69,184,224,225], to our knowledge only a handful of studies have investigated the effects of an instruction-based external focus for patients rehabilitating from ACLR [5,77]. Notably, other studies have successfully used augmented feedback techniques to improve ACL injury risk biomechanics via visual stimuli presentation of video feedback compared to or in place of verbal, externallyfocused feedback [28,29,67,68,157].…”
Section: Pillar 3: An External Focus Of Attentionmentioning
confidence: 99%
“…Journal of Science in Sport and Exercise (2021) 3:[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] …”
mentioning
confidence: 99%
“…In tasks of a closed nature, it is easier to identify the optimal movement technique, taking into account that factors exogenous to the athlete (or environmental factors) play a less important role in the modelling equation [ 17 ]. On the other hand, numerous authors have used an expert model to correct sports technique [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%